Immunodeficiency caused by cirrhosis - Tuchendler, Ewelina; Tuchendler, Paweł K.; Madej, Grzegorz (Clinical and Experimental Hepatology, 2018)
The syndrome of decreased immunity caused by cirrhosis is a combination of different immunological mechanisms and reactions which result from an advanced stage of the liver disease. The synthesis of proteins of the acute phase becomes impaired, there develop different deficiencies of the complement system, and there ensues a decrease of receptors that are meant to recognize antigens. The negative changes become apparent in the field of cell responses, e.g. there are changes in the amounts of generated monocytes and macrophages, and their phagocytic capabilities and chemotaxic reactions are impacted as well. The humoral response results in distorted synthesis of particular antigen categories. The risk of detrimental immunoresponses with the end result of endotoxemia is not rarely coupled with both local and global infections. The combination of the aforesaid immunodeficiencies worsens the healing chances of cirrhosis sufferers and more often than not it increases the mortality of the affected patients.